Physical Activity in Pregnancy: The Role of Exercise in Promoting Maternal and Fetal Health - Michalina Dubińska; Wiktoria Paduch-Jakubczyk; Wiktoria Bilska; Urszula Ciułek; Anna Dobosz; Wiktoria Zduńczyk; Ada Żydek (Nicolaus Copernicus University in Toruń, 2024)
Introduction and Objective:  There is no doubt that engaging in regular physical activity is beneficial for individuals of all ages. Pregnancy is a special time of life for most women. This period presents a unique opportunity for them to improve their lifestyle choices and adopt healthier habits such as exercise. The aim of this article is to find out if regular physical activity during pregnancy has a positive impact for both the mother and the baby. Review and Methods: Review and summary of available studies and meta-analyses found in open-access formats on Google Scholar and PubMed. State of Knowledge: The WHO defines physical activity as any bodily movement requiring energy expenditure, including during leisure, transport, work, and domestic activities. Regular exercise reduces the risk of noncommunicable diseases (NCDs) and poor health outcomes, while sedentary behavior contributes to this and burdens healthcare systems. For pregnant and postpartum women, physical movement decreases the risk of various complications, with no negative effects on birthweight or stillbirth risk. Conclusions: Studies show that physical activity decreased risk of pre-eclampsia, gestational hypertension, gestational diabetes, excessive gestational weight gain, delivery complications, postpartum depression and newborn complications.